Psychologically-Based Criteria for Classification by Motif and Tale Type. - El-Shamy, Hasan M. (Journal of Folklore Research)
The article discusses psychologically-based criteria for classification by motif and tale type. The introduction of psychologically-based motifs and tale-types can help shed light on the processes involved in lore's description of life and living, in general. These portrayals constitute cognitions out of which a social group forms its views and attitudes on "how things are" or "ought to be." The relationship between the study of lore and the discipline of psychology should be reciprocal. Lore can provide psychologists with issues to be studied as well as with feedback on the validity of their laboratory findings.